Husk tomato cultivars susceptible to wilt in Sinaloa - Ayala-Armenta, Quintín Armando; Peinado-Fuentes, Luis Alberto; Beltrán-Peña, Hugo; Tovar-Pedraza, Juan Manuel; Valenzuela-Escoboza, Fernando Alberto; Ruelas-Islas, Jesús del Rosario (Revista Mexicana de Ciencias Agrícolas, 2024)
The wilt or damping-off of husk tomato is a disease caused by fungi originating in the soil, among which Fusarium oxysporum, Macrophomina phaseolina, and Rhizoctonia solani stand out, causing losses due to the lack of resistant varieties. This study aimed to determine the response of husk tomato (Physalis ixocarpa Brot.), Dalí, Siqueiros, and Tamayo hybrids, as well as cv. Gabriela, Puebla, San Miguel, and Tecozautla, to pathogenic isolates of F. oxysporum, M. phaseolina, and R. solani. The study was conducted under greenhouse conditions; sterilized substrate of river sand + peat (1:3 v/v) was placed in pots and then inoculated with three isolates of F. oxysporum 1.6x105 CFU, two of M. phaseolina, and three of R. solani (8 g of infested sorghum seed/pot, of each fungus). Five seeds of the corresponding husk tomato cultivar were deposited in each pot, then covered with the same substrate and incubated for 30 days. A completely randomized design was used, with three repetitions (pots). In the control treatment, the seeds were sown on soil without fungus. The emergence of seedlings was estimated nine days after sowing (das), and the severity of infection for each of the pathogens (scale of 0-5) at 30 das. Data were analyzed using nonparametric statistics. The seven cultivars tested were susceptible to the species F. oxysporum, M. phaseolina, and R. solani; some of the isolates tested exerted a significant differential effect of virulence on some of the varieties studied.
Keywords: Fusarium oxysporum; Macrophomina phaseolina; Rhizoctonia solani; husk tomato cultivars; pathogenicity